A randomized phase 2 trial of first-line docetaxel, carboplatin, capecitabine (CTX) and epirubicin, oxaliplatin, capecitabine (EOX) in advanced esophagogastric adenocarcinoma. (3rd July 2021) - Petersen, Peter C.; Petersen, Lone N.; Vogelius, Ivan; Bjerregaard, Jon K.; Baeksgaard, Lene
Abstract: Background: No preferred first-line chemotherapy regimen exists for advanced esophagogastric adenocarcinoma. Addition of docetaxel to cisplatin and 5-fluorouracil (DCF) has been shown to improve survival but is associated with increased toxicity. In this randomized, non-comparative phase 2 trial, we tested carboplatin, docetaxel, and capecitabine (CTX), a potentially useful modification of DCF (NCT02177552). Patients and methods: Patients with advanced HER2-negative esophagogastric adenocarcinoma not previously treated in the first-line setting were randomized to intravenous docetaxel 60 mg/m 2 and carboplatin AUC5 plus oral capecitabine 1000 mg/m 2 bd days 1–14, q4w (CTX) or intravenous epirubicin 50 mg/m 2 and oxaliplatin 130 mg/m 2 on day 1 plus oral capecitabine 625 mg/m 2 bd days 1–21, q3w (epirubicin, oxaliplatin and capecitabine [EOX]). Treatment continued until progression, intolerance or for a maximum of nine cycles. The primary endpoint was 1-year survival for patients treated with CTX. Results: Between June 2014 and January 2019, a total of 98 eligible patients were randomized. The 1-year survival rate was 34.7% (95% CI 21.8 − 47.9) with CTX and 36.7% (95% CI 23.6 − 50.0) with EOX. Progression-free survival and overall survival were 6.1 months (95% CI 5.5 − 7.1) and 9.8 months (95% CI 8.2 − 11.0) with CTX and 5.1 months (95% CI 4.3 − 7.0) and 10.2 months (95% CI 8.0 − 11.9) with EOX, respectively. Related grade 3 or 4 treatment-emergent adverse events (AEs) occurred in 86% of patients on CTX and 69% on EOX. Febrile neutropenia occurred in 31.4% of patients on CTX and 13.7% on EOX. Conclusions: First-line CTX showed insufficient efficacy and caused a high rate of febrile neutropenia. CTX could not, therefore, be recommended for further study. This trial adds to current knowledge of docetaxel combined with platinum and 5-FU: that the combination is associated with increased toxicity and its use should be limited to fit patients in need of a response.